2021
DOI: 10.22331/q-2021-03-10-408
|View full text |Cite
|
Sign up to set email alerts
|

Second law of thermodynamics for batteries with vacuum state

Abstract: In stochastic thermodynamics work is a random variable whose average is bounded by the change in the free energy of the system. In most treatments, however, the work reservoir that absorbs this change is either tacitly assumed or modelled using unphysical systems with unbounded Hamiltonians (i.e. the ideal weight). In this work we describe the consequences of introducing the ground state of the battery and hence — of breaking its translational symmetry. The most striking consequence of this shift is the fact t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In this presentation, all qubit erasure processes take place in the computational registers. It is possible to outsource this thermodynamic task to an external battery register [6,[25][26][27]. The battery consists of fueled qubits in state |0 and depleted qubits in the fully mixed state 1/2; the erasure of depleted qubits takes place there at temperature T , with an average work cost of k B T ln 2 per qubit.…”
Section: Discussionmentioning
confidence: 99%
“…In this presentation, all qubit erasure processes take place in the computational registers. It is possible to outsource this thermodynamic task to an external battery register [6,[25][26][27]. The battery consists of fueled qubits in state |0 and depleted qubits in the fully mixed state 1/2; the erasure of depleted qubits takes place there at temperature T , with an average work cost of k B T ln 2 per qubit.…”
Section: Discussionmentioning
confidence: 99%
“…In general, for the coherent work operator (i.e., with the non-vanishing commutator (24)), the expansion of the operator MS (t) is equal to:…”
Section: Momentsmentioning
confidence: 99%
“…Consequently, we possess a framework with an explicit work reservoir that recreates all of the fluctuation theorems just by this symmetry (cf. [24] where are discussed corrections if translational invariance is violated). Moreover, it has also been shown that the optimal work extracted by the quantum weight is limited by the ergotropy [19,25], which, with the notion of passivity, is another building block of quantum thermodynamics (see, e.g., [26,27]).…”
Section: Introductionmentioning
confidence: 99%
“…Other works have introduced different models of batteries, including a two-level wit [8], a weight with discrete spacing [22] or energies bounded from below [45], which lead to additional constraints on the initial state or different results in terms of work extraction. Our motivation for considering the model above is it leads to a simple model, with the closest parallels to classical thermodynamics.…”
Section: A Explicit Batteriesmentioning
confidence: 99%